A new Hyphessobrycon (Characiformes: Characidae) of the Hyphessobrycon heterorhabdus species-group from the Central Amazon basin, Brazil - Faria, Tiago C.; Bastos, Douglas A.; Zuanon, Jansen; Lima, Flávio C.t. (Zootaxa, 2020)
A new species of Hyphessobrycon Durbin from the Paraná do Urariá system in Central Amazon region, Amazonas state, Brazil, is described. The new species is allocated into the Hyphessobrycon heterorhabdus species-group due to its color pattern, composed by a well-defined, horizontally elongated humeral blotch continuous with a conspicuous midlateral dark stripe that becomes blurred towards the caudal peduncle, and can be distinguished from all other species of the group by possessing humeral blotch and continuous midlateral stripe broad, occupying vertical height equivalent of two scale rows. A tricolored pattern composed dorsally by a red or reddish longitudinal stripe, a middle iridescent, golden or silvery longitudinal stripe, and ventrally by a variably-developed longitudinal dark stripe is identified as a putative additional character shared by the species of the Hyphessobrycon heterorhabdus species-group. The presence of bony hooks in all fins in mature males of some species of the Hyphessobrycon heterorhabdus species-group is also discussed.